La política de la comunión de Jean-Luc Marion - Vinolo, Stéphane (2024)
Among all the fields covered by Jean-Luc Marion’s phenomenology of givenness, it is remarkable that politics occupies a scarce, if not non-existent, place. This quasi-absence can be explained by conceptual reasons, given that political philosophy is enclosed within metaphysics through its recurrent use of concepts such as the subject, the power or the interests. However, it is possible to think, from Marion’s philosophy, a politics that is not limited to his metaphysical figure. This possibility supposes a true politics of communion that unites the collective from a point that remains external to it and that does not serve as its foundation.